2008
DOI: 10.1016/j.ajo.2008.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Early Retinal Vascular Abnormalities in African-American Cocaine Users

Abstract: Purpose-To evaluate early changes in the central retinal response in HIV positive patients without infectious retinitis using multifocal electroretinography (mfERG).Design-The study was a case control study.Methods-We evaluated three cohorts -HIV negative controls and two groups of HIV positive patients separated according to their nadir CD4 counts (≥100 and <100 for a minimum of 6 months). MfERG first (FOK) and second order (SOK) kernels were analyzed separately by areas of rings, quadrants and individual hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Significant variables from the univariate analyses were then incorporated into a multivariate GLMM for each dispersal mechanism. Model selection was based on the selection of independent variables that contributed significantly to each final GLMM sub‐model (Pinheiro & Bates 2000; Leung et al. 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant variables from the univariate analyses were then incorporated into a multivariate GLMM for each dispersal mechanism. Model selection was based on the selection of independent variables that contributed significantly to each final GLMM sub‐model (Pinheiro & Bates 2000; Leung et al. 2008).…”
Section: Methodsmentioning
confidence: 99%
“…vertebrate ingestion, vertebrate attachment, vertebrate both and ballistic)Leung et al 2008). All GLMM were constructed with a binomial response variable and a logit-link function.…”
mentioning
confidence: 99%
“…[34] In a study comparing African-American patients who used cocaine with those who did not use cocaine, investigators found a wider retinal venular caliber and increased arterial branching, and proposed this may reflect more generalized central nervous system (CNS) microvascular disease. [35]…”
Section: Retinamentioning
confidence: 99%